A novel transient gravimetric monitoring technique implemented to GCL osmotic suction control. Issue 6 (December 2020) - Acikel, A.S.; Bouazza, A.; Gates, W.P.; Singh, R.M.; Rowe, R.K.
Abstract: A modified osmotic suction control technique for monitoring apparent transient weight changes was successfully adapted to the wetting and drying paths of geosynthetic clay liners (GCLs). Reasonable control was possible, enabling suction equilibrium to be achieved without disruption to the test. The results provide unique insight into the time-dependent changes in water retention properties and the semi-permeable membrane behaviour of the bentonite component in GCLs. The stages of suction equilibrium, related to the tri-modal pore structure of GCLs and the point of capillary break, could also be monitored. While the osmotic method has been traditionally used to control matric suction (up to 10 MPa) in soils, the overall results presented in this paper indicate that its application for total suction control in GCLs is largely due to the membrane behaviour of their bentonite component. Furthermore, because of capillary break between the GCL and the osmotic solution at the water entry (or residual) suction value of a GCL, an upper limit of 2.8 MPa suction is recommended for the application of the osmotic method to measure the water retention properties of GCLs. Highlights: Real-time transient weight change monitoring was implemented on osmotic suction control of GCL on wetting and drying paths. Capillary break, suction equilibrium, and time dependency were monitored without specimen disturbance. Osmotic technique is recommended for total (instead of matric) suction control of GCLs due to bentonite membrane behavior. Osmotic technique has an applicable upper limit of 2.8 MPa corresponds to GCL water entry (residual) suction value.